Rancang Bangun Sistem Informasi Katalog Digital Aplikasi Pemerintah Kabupaten Garut Berbasis Website - Alif Mildani; Elin Rosliani (Masoem University, 2026)
The management of inventory and the dissemination of information related to e-Government applications within the Garut Regency Government are still carried out conventionally, which impacts low internal efficiency and a lack of transparency to the public. Therefore, this study focuses on the design and development of a Web-Based Digital Catalog Information System for Applications to serve as a centralized information platform solution. The methodology adopted for system development is the System Development Life Cycle (SDLC) Waterfall model, with code implementation utilizing the Laravel Framework and MySQL Database. The resulting system successfully integrates essential features, including Data Management (CRUD) capabilities for the administrator, as well as Search and Category Filtering functions accessible to the public. Functional verification of the system was performed through Black Box Testing, which demonstrated a 100% validation rate for the core functionalities. This system is proven effective in supporting the increase of internal operational efficiency within the Garut Regency Government and simplifying public access to application inventory information.